Sistematization of perioperative care - a qualitative research - Luciana Grittem; Marineli Joaquim Meier; Aida Maris Peres (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <style>
/* Style Definitions */
table.MsoNormalTable
{mso-style-name:"Tabela normal";
mso-tstyle-rowband-size:0;
mso-tstyle-colband-size:0;
mso-style-noshow:yes;
mso-style-parent:"";
mso-padding-alt:0cm 5.4pt 0cm 5.4pt;
mso-para-margin:0cm;
mso-para-margin-bottom:.0001pt;
mso-pagination:widow-orphan;
font-size:10.0pt;
font-family:"Times New Roman";}
</style> <![endif]-->Qualitative study which objectified to develop a cooperative process in order to structure perioperative nursing at the surgical unit of a hospital in Curitiba/Brazil. Action-research was the methodology used with seven nurses from the surgical unit. The following thematic categories emerged: organizational structure hindering nurses' decision-making; basic conditions for perioperative nursing care; caring/managerial nursing work process in the surgical unit; caring/managerial nursing attributions in the surgical unit; perioperative nursing instrument; inclusion of nursing diagnosis in the perioperative nursing instrument; relevant information for the transoperative phase; immediate post-operative period as the action setting for perioperative nursing. The discussion process enabled the reflection on perioperative nurses' professional practice as well as their actions towards professional recognition.